Peran Religiuitas dan Word of Mouth terhadap Keputusan Nasabah dalam Memilih Bank Syariah Indonesia dengan Motivasi sebagai Variabel Moderasi - La Sudarman; La Jejen; Husriah Husriah (Jurnal Bisnis dan Manajemen, 2022)
The Purpose of this study is to determine the effect of religiosity, word of mouth and motivation on customer decisions to choose Islamic banks, as well as the influence of religiosity and word of mouth on customer decisions to choose Islamic banks with motivation as moderation. The method used is a quantitative approach and analysis using SEM-PLS. The sampling technique used the census method as many as 120 consumers who used the services of Bank Syariah Indonesia Baubau branch. Based on the results of the study, it shows that religiosity, word of mouth, motivation have a significant effect on customer decisions to choose Islamic banks. Meanwhile, the influence of religiosity is moderated by motivation on customer decisions, showing negative results, meaning that motivation does not moderate the relationship of religiosity to customer decisions; and the effect of word of mouth on customer decision variables moderated by motivational variables shows that motivation moderates the influence of word of mouth on customer decisions.